Eletrofiação de blendas de Ecovio® na presença de óleo essencial de melaleuca: produção de bandagens para aplicação biomédica - Souza, Bianca Zarske de (2022)
Data lesions are susceptible to the adhesion and occurrence of bacteria, being possible the adhesion of infections. Skin lesions cause pain and discomfort in the human body and this happens mainly with those that take longer to heal. Therefore, the development of polymeric bandages, through the electrospinning technique, with antimicrobial activity, has been highlighted, as these materials can protect the lesion from microbial contamination, enabling the healing process. This study shows, for the first time, the development of fibers with favorable properties for the application of biodegradable bandages based on the Ecovio® (EC) blend composed of poly (lactic acid) (PLA) and poly (adipate-co-butylene terephthalate) (PBAT) incorporated with Essential Oil of Melaleuca (OM). OM, with antimicrobial activity against Pseudomonas aeruginosa (P. aeruginosa) and Staphylococcus aureus (S. aureus), was associated with EC blend (10% w/v) in binary mixtures of chloroform and formic acid (85/15 v/v). EC/OMx fibers were characterized by Scanning Electron Microscopy (SEM), contact angle measurements, mechanical properties measurements, Fourier Transform Infrared Spectroscopy (FTIR), X-ray excited photoelectron spectroscopy (XPS) and differential scanning calorimetry (DSC). The tests showed that the OM (1.5 mL and 75.00 %m), in relation to the EC mass in the blend solution, increased EC electrospinability, leading to the formation of more homogeneous fibers with an average diameter of 278 nm. OM (75% m) increased EC fiber wettability from 120±2° to 69±1°. Preliminary bacterial adhesion and proliferation assays showed that EC/OM fibers have antimicrobial activity against P. aeruginosa and S. aureus, after 24h of incubation. Compatibility assays with human blood (platelet adhesion and clotting) indicated that EC/OM fibers can accelerate the blood clotting process. EC/OM fibers present interesting chemical and biological properties (in vitro) to be applied as bandages.